2021
DOI: 10.1002/ecm.1476
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and behavioral mechanisms of density‐dependent habitat expansion in a recovering African ungulate population

Abstract: Major disturbances can temporarily remove factors that otherwise constrain population abundance and distribution. During such windows of relaxed top-down and/or bottom-up control, ungulate populations can grow rapidly, eventually leading to resource depletion and density-dependent expansion into less-preferred habitats. Although many studies have explored the demographic outcomes and ecological impacts of these processes, fewer have examined the individual-level mechanisms by which they occur. We investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 85 publications
0
26
0
Order By: Relevance
“…Today, numerous projects are underway in GNP. These studies use a combination of methods including motion-triggered cameras (Gaynor et al, 2018(Gaynor et al, , 2021Easter et al, 2019), biologgers (often including Global Positioning System units, triaxial accelerometers, and sometimes video recorders; e.g., Branco et al, 2019a,b;Becker et al, 2021;Bouley et al, 2021), aerial counts (Cumming et al, 1994;Dutton and Carvalho, 2002;Dunham, 2004;Stalmans, 2012;Stalmans et al, 2019), animal follows (Hammond et al, 2022), molecular studies (Martinez et al, 2019;Santander et al, 2022), and other field observation tools (e.g., Muschinski et al, 2019) to gain insights in the park's ecology. The δ 13 C enamel , δ 15 N enamel , and δ 18 O enamel datasets of Gorongosa's fauna presented here-the first stable isotopes result for any terrestrial fauna in Mozambique-will help us to better understand dietary patterns of the large-bodied animals which roam GNP today.…”
Section: Greater Kudumentioning
confidence: 99%
“…Today, numerous projects are underway in GNP. These studies use a combination of methods including motion-triggered cameras (Gaynor et al, 2018(Gaynor et al, , 2021Easter et al, 2019), biologgers (often including Global Positioning System units, triaxial accelerometers, and sometimes video recorders; e.g., Branco et al, 2019a,b;Becker et al, 2021;Bouley et al, 2021), aerial counts (Cumming et al, 1994;Dutton and Carvalho, 2002;Dunham, 2004;Stalmans, 2012;Stalmans et al, 2019), animal follows (Hammond et al, 2022), molecular studies (Martinez et al, 2019;Santander et al, 2022), and other field observation tools (e.g., Muschinski et al, 2019) to gain insights in the park's ecology. The δ 13 C enamel , δ 15 N enamel , and δ 18 O enamel datasets of Gorongosa's fauna presented here-the first stable isotopes result for any terrestrial fauna in Mozambique-will help us to better understand dietary patterns of the large-bodied animals which roam GNP today.…”
Section: Greater Kudumentioning
confidence: 99%
“…This may be attributed to a shortage of grass availability and nutritional quality (Copeland et al, 2008) in the dry season and could also be due to low nutritional value of the plant species. Becker et al (2021) reported that waterbuck routinely forage on forbs and subshrubs throughout their range. Kassa et al (2007) found waterbuck diet to be less diverse during the dry season and much more varied during the rainy season.…”
Section: Resultsmentioning
confidence: 99%
“…This is coherent with the findings of Okello et al (2015) in the Kenya‐Tanzania border where the authors reported that in the dry season about 32% of the 24‐h day was spent in browsing (eating leaves, small shoots, and fruits), whereas no time was spent on it during the wet season. Gutbrodt (2006) and Kassa et al (2007) reported that although the diet of waterbuck consists mainly of grasses, browse and forbs are also consumed while Becker et al (2021) found that waterbuck routinely forage on forbs and subshrubs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These processes can regulate megafauna populations and influence their distribution within the broader landscape 22,23 . Megafauna, in turn, can have a significant impact on vegetation structure, composition 24 , and ecosystem processes and functioning, such as foraging, trampling, and nutrient/seed dispersal 25,26 . Megafauna conservation using (large) PAs is partly based on the assumption that all these natural processes will continue to drive megafauna population dynamics by preventing unsustainable human influences within PA borders 27 .…”
Section: Natural Vs Human Driversmentioning
confidence: 99%